PEMIKIRAN SYEKH NAWAWI AL-BANTANI DALAM BIDANG HUKUM ISLAM (Tentang Taklif dan Mukalaf) - Khusaeri Khusaeri (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2014)
Sheikh Nawawi was born in 1815 by the name Abu „Abd al-Mu‟thi Muhammad Nawawi Ibn „Umar al-Tanari Al-Bantani al-Jawi. Ashis name implies, Java Island was his birthplace. It was in the village ofTanara in Banten district of West Java. When he was fifteen, the sheikhengaged in a pilgrimage to Mecca and he found interests in thescientific life there in the Holy City for the Muslims. Drawn to theliking of intellectual life as religious scholar in Mecca, the sheikhdecided to deepen his religious study in the city for three years. Whenthe sheikh journeyed for his second pilgrimage to Mecca, he decided tocontinue his study and to be the permanent resident of the Holy City.During his scholarly life, Sheikh Nawawi had authored 99 to 115religious books with various topics and themes. As the sheikh was thedisciple of Madhhab Shafi‟i, the religious books he authored were ofthe madhhab. In his discussion on taklif and mukallaf, those bearingthe taklif, for instance, the sheikh said that the taklif from Allah neverburdens mankind; the taklif is always in concordance with the abilitiesmen possess (Al-Baqarah 286).